Dissection of the sequence-specific DNA binding and exonuclease activities reveals a superactive yet apoptotically impaired mutant p53 protein - Ahn, Jinwoo (2009)
Both sequence-specific DNA binding and exonuclease activities have been mapped to the central conserved core domain of p53. To gain more information about these two activities a series of mutants were generated that changed core domain histidine residues. Of these mutants, only one, H115N p53, showed markedly reduced exonuclease activity (ca. 15% of wild-type). Surprisingly, purified H115N p53 protein was found to be significantly more potent than wild-type p53 in binding to DNA by several criteria including gel mobility shift assay, filter binding and DNase I footprinting. Interestingly as well, non-specific DNA binding by the core domain of H115N p53 is superior to that of wild-type p53. To study H115N p53 in vivo, clones of H1299 cells expressing tetracycline regulated wild-type or H115N p53 were generated. H115N was both more potent than wild-type p53 in inducing p53 target genes such as p21 and PIG3 and was also more effective in arresting cells in G1. Unexpectedly, in contrast to wild-type p53, H115N p53 was markedly impaired in causing apoptosis when cells were subjected to DNA damage. Our results indicate that the exonuclease activity and transcriptional activation functions of p53 can be separated. They also extend previous findings showing that cell cycle arrest and apoptosis are separable functions of p53. Finally, these experiments confirm that DNA binding and xonuclease activities are distinct features of the p53 core domain.